Plastic embedded core biopsy: a complementary approach to bone marrow aspiration for diagnosing acute myeloid leukaemia. Issue 3 (March 1989) - Islam, A; Frisch, B; Henderson, E S
Abstract : Bone marrow aspirates and biopsy specimens were taken at diagnosis from 51 patients with acute myeloid leukaemia (AML). The diagnosis was based on morphological and cytochemical analyses, and the leukaemias were classified by FAB criteria. A considerable difference was observed between the results of bone marrow aspirates and the findings of plastic-embedded bone marrow biopsy specimens, particularly in marrow cellularity, extent of blast cell infiltration, and cell type involved in the leukaemic process. The myelomonocytic cell type seemed to predominate in the sections. In four cases there was considerable marrow infiltration with maturing, but dysplastic, granulocytic cells in the sections, but not in the aspirate smears. Features of potential prognostic importance, such as bone marrow infiltration with inflammatory cells, were easily recognised and quantified in the sections. These results indicate that plastic embedded bone marrow biopsy sections complement the findings of bone marrow aspiration in the diagnosis of AML and may also provide information of independent prognostic importance that cannot be obtained by other means.